Comparative effects of hydralazine and captopril on the cardiovascular changes in spontaneously hypertensive rats. - Limas, C. (1984)
Vascular changes that develop during the course of blood pressure rise in spontaneously hypertensive rats (SHRs) can be modified by antihypertensive therapy. It is not known, however, whether there is selectivity in the structural response to specific antihypertensive drugs. This issue was examined by comparing the effects of a direct vasodilator (hydralazine) and a converting enzyme inhibitor (captopril) on morphologic aspects of the cardiovascular system. Male SHRs, 21 weeks of age, were given either hydralazine (HCl plus hydrochlorothiazide, captopril plus hydrochlorothiazide, or hydrochlorothiazide alone. Untreated age-matched SHRs and Wistar-Kyoto normotensive rats (WKYs) were used as controls. Animals were sacrificed at 27-28 weeks of age. Both hydralazine and captopril lowered significantly the blood pressure of SHRs, whereas hydrochlorothiazide alone was ineffective. The heart/body weight ratios were dramatically reduced in captopril-treated SHRs to below the level of WKYs; hydralazine induced only a very modest (5%) reduction, whereas the diuretic alone was ineffective. The morphology of the aortic intima improved dramatically in response to captopril and hydralazine and, to a lesser extent, hydrochlorothiazide alone. This effect becomes apparent within 6 weeks of treatment, and the only evidence of preexisting disease is the persistence of collagen in the subendothelium. Captopril and hydralazine, but not hydrochlorothiazide alone, reduce the thickness of the aortic media below that of normotensive controls. In addition, captopril and hydralazine improve the structure of small intrarenal vessels. There was a strong correlation between the relative effectiveness of the three pharmacologic agents in lowering blood pressure and in improving the changes of intrarenal vessels. These results highlight the capacity of antihypertensive therapy to arrest or reverse the structural sequelae of hypertension. In addition, they underscore the heterogeneity in the response of different components of the cardiovascular system, which, in part, reflects selectivity in the action of antihypertensive agents.